Print Advertising of Educational Services: an investigation on the impact of the pictures facilities and testimonial about attitudes - Ayrosa, Eduardo André Teixeira; Facó, Marcos Henrique (Review of Business Management, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Just like other services organizations, some higher education institutions have invested in printed advertising to attract applicants. The services management literature suggests that using stimuli such as pictures of the facilities and alumni testimonials may help to turn tangible the offer of services so strongly intangible as higher education. In the present work, the impact of two different types of cue on prospects’ attitudes is investigated. The cue paradigm (Olson & Jacoby 1972) has been used to select the two types of cue: intrinsic (facilities pictures), and extrinsic (testimonials). An experiment has been conducted not only to assess the effect of the impact of four levels of presence of cues (absent, only intrinsic, only extrinsic, both) on prospects’ attitudes, but also the effect of prospects’ involvement level with higher education organizations on each of the four conditions. Results show that although there were no differences detected between the effects of four types of argument about public attitudes, respondents with low involvement in the dimension values/self image has showed more favorable attitudes regarding the (intentions of enrollment) when exposed to testimonials (extrinsic cue). Key words: Educational services advertising, Cue paradigm. Physical representation and association strategies. Attitudes.